(untitled) (Journal Of Educational and Psychological Researches, 2012)
Arabic calligraphy is one of the ancient arts rooted in history, And that he grew up conflicting views and writings addressed as a, communication tool for the linguistic The teaching calligraphy note an art and science because it depends on the fixed assets and precise rules in his art because centered Beauty It targets teach Arabic calligraphy speed as the education and recitation helps to write fast Which have great interest in the field of education and in life both Also accompanied Arabic calligraphy and scientific renaissance significant knowledge in the Arab-Islamic civilization deeply embodied in the paintings and manuscripts bearing features of Arabic art and oriental spirit net purity Teaching Arabic calligraphy, there is no specific way for To teach specific Arabic calligraphy and all modalities that emerged in recent years were the result of both changing perceptions regarding the main purposes of learning all the way advantages and disadvantages and its supporters In this regard, the teaching Arabic Calligraphy needs for a limited time devoted to teaching .